Os sentidos de família no fantástico : destacabilidade e aforização - Mendes, Maria Danielle (2010)
In the middle of the significant changes in culture, politics, economy and technology during the last decades, the family institution is still considered a social reference, now constituted and behavior-based accordingly with post-modernity. Besides traditional families, which maintain values as official marriage and the presence of a male and a female genitor, we cohabit with heterogenic models of families, which do not have the need to civil or religious marriage, do not have necessarily the mother or the father figure, and admits being formed by homosexual or childless couples. These are manifestations of the multiple facets of the same institution which moves into different discourses and contributes to the transformation in the concept of family. Based on theoretical conjectures of the French Discourse Analysis in Dominique Maingueneau´s perspective (1995, 1996, 1997, 1998, 2005, 2008-c, 2008-d, 2008-e, 2008-f, 2010), we propose to answer the following question: in which way highlight enunciations at Fantástico electronic magazine contribute to the constitution and circulation of the concept of family? The present work is composed by a series of five special packages broadcasted in August 2008, when the program celebrated its 35th anniversary. Each one of the packages is based on a scenario that links news, interviews, and dramatization. In order to answer our research question, we worked with the notion of discursive ethos, enunciated scene, constituted heterogeneity of discourse and especially highlights, (MAINGUENEAU, 2008-d), personal and sententious aphorism, which enables to relate the group of emphasized phrases in Fantástico to the way of being and saying that is crystallized into the society. Once the acknowledgement of the discursive facts links to the real historic and social recognition, the analysis of the series is simultaneously the analysis of the private life on contemporary Brazil. We conclude that the highlights inside Fantástico´s discourse promote relations between the new conception of family with the traditional one, and contributes to the ethos of the program. In this way, however innovative the discourse about family may seem, it keeps traces of the discursive speech connected to the traditional concept of family. The relevancy of this research consists in analyzing this new way of broadcasting the constitution of family and its relations, as well as deepening the theoretical discussion on the concept of the highlight enunciation.